Muscle Mass in Children and Adolescents: Proposed Equations and Reference Values for Assessment - Cossio Bolaños, Marco A.; Andruske, Cynthia Lee; de Arruda, Miguel; Sulla-Torres, Jose; Urra-Albornoz, Camilo; Rivera-Portugal, Margot; Luarte-Rocha, Cristian; Pacheco-Carrillo, Jaime; Gómez-Campos, Rossana (Frontiers in Endocrinology, 2019)
Objectives: The goal of this study was to develop regression equations to estimate LM with anthropometric variables and to propose percentiles for evaluating by age and sex. Methods: A cross sectional study was conducted with 2,182 Chilean students (1,347 males and 835 females). Ages ranged from 5.0 to 17.9 years old. A total body scan was carried out with the double energy X-ray anthropometry (DXA) to examine and measure lean muscle mass of the entire body. Weight, height, and the circumference of the relaxed right arm were also measured. Results: Four anthropometric equations were generated to predict lean mass for both sexes (R2= 83-88%, SEE= 3.7-5.0%, precision = 0.90-0.93, and accuracy = 0.99). The Lambda-mu-sigma method was used to obtain the sex-specific and age-specific percentile curves of lean mass (p3, p5, p10, p15, p25, p50, p75, p85, p90, p95, and p97). Conclusion: The four proposed equations were acceptable in terms of precision and accuracy to estimate lean mass in children and adolescents. The percentiles were created by means of anthropometric equations and real values for DXA. These are fundamental tools for monitoring LM in Chilean children and adolescents of both sexes.